Pemanfaatan Film Animasi Dengue Hemorrhagic Fever Selama Masa Pandemi Covid-19 - Septa Katmawanti; Muhammad Al-Irsyad; Farah Paramita; Fandi Achmad Saputra; Dea Aflah Samah; Gladys Cyntya Mahardyka; Purnama Devita Sari; Belisa Fitria Az Zahra Bachtiar (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
The number of cases of Dengue Hemorrhagic Fever (DHF) in Malang Raya during the COVID-19 pandemic has increased. This is due to the Large-Scale Social Restriction Program (PSBB), so that efforts to tackle the spread of DHF cannot run optimally. This study aims to create an animated film that facilitates education to the people of Malang Raya regarding efforts to prevent and control dengue outbreaks in the pandemic period and in the future. The research methodology is carried out using research and development methods which are divided into two major parts, namely product design and product design in the form of animated films. Research respondents consisted of 16 respondents with an age range of 15-21 years. The results showed that most of the respondents had never watched a DHF animated film. Respondents' responses indicated that there was a potential increase in dengue fever sufferers during the COVID-19 pandemic caused by low self-awareness such as ignoring the quality of their health when studying at home. Suggestions for the DHF animated film are to add information on how to drain the bathtub properly on a regular basis, bury used items that are no longer used, plant mosquito repellent plants, use insect repellent, and create posters or content about dengue fever.